2016
DOI: 10.4238/gmr.15038575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the species Salvinia (Salviniaceae) from the upper Paraná River floodplain

Abstract: ABSTRACT. The pteridophytes Salvinia minima, S. herzogii, and S. auriculata are among the most abundant aquatic macrophytes in the upper Paraná River floodplain. Since some species have highly similar morphological features, it is very difficult to identify members of this genus to the species level. An indication of this difficulty is a set of poorly differentiated taxa comprising S. auriculata and S. herzogii known as the 'S. auriculata complex', which is found in the Paraná River together with other Salvini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results also showed that the trnL-trnF region varied between Piper species, reinforcing other studies on this region, which is quite diverse in size and composition, so it is widely used for the reconstruction of phylogenetic patterns in plants (Hilu & Liang, 1997). According to Machado, Oliveira, Fabrin, Prioli, and Prioli (2016), the trnL-trnF spacer in Salvinia species proved to be efficient in distinguishing close species. Ng, Sandoval and Murphy (2016) studied this same region in Lophophora and reported this region behaved as a good molecular marker for differentiation of species and genera, supporting our findings.…”
Section: A G C T a G C T G T G A C C G A A A T C C C T T T A G A A A ...supporting
confidence: 78%
“…The results also showed that the trnL-trnF region varied between Piper species, reinforcing other studies on this region, which is quite diverse in size and composition, so it is widely used for the reconstruction of phylogenetic patterns in plants (Hilu & Liang, 1997). According to Machado, Oliveira, Fabrin, Prioli, and Prioli (2016), the trnL-trnF spacer in Salvinia species proved to be efficient in distinguishing close species. Ng, Sandoval and Murphy (2016) studied this same region in Lophophora and reported this region behaved as a good molecular marker for differentiation of species and genera, supporting our findings.…”
Section: A G C T a G C T G T G A C C G A A A T C C C T T T A G A A A ...supporting
confidence: 78%
“…A recent molecular study on the Salvinia species in the Upper Parana River only looked at a single cpDNA region (trnL‐trnF) and compared their findings with existing GenBank sequence data (Machado et al, 2016). Plants identified as S. auriculata and S. herzogii clustered with molecular data for S. oblongifolia and S. molesta respectively that were cultivated in botanical gardens (Nagalingum et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study the trnL-trnF was not used for analysis. Unfortunately the newly generated sequence data of the Machado et al (2016) study is not deposited in GenBank so we could not compare the potentially additional S. auriculata data with our analysis. The quality of the generated trnL-trnF DNA sequence of our herbarium samples of S. auriculata was not sufficient to perform a reliable analysis.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…The correct identi cation of invasive aquatic plant species and information on their genetic variability are fundamental to understanding the mechanism of invasion (Naugzemyz et al 2021) and implementing management strategies, as well as research into potential control agents, including biological ones (Pitelli et al 2008). Molecular tools have been useful for the correct identi cation and analysis of genetic variability in macrophyte populations, including Urochloa in the Upper Paraná River basin (Machado et al 2016;Lucio et al 2019;Diamante et al 2020) and in other watersheds (Collevatti et al 2003;Cloutier et al 2005;Azevedo et al 2008). A previous study with U. arrecta in Itaipu reservoir (Brazil) showed a high degree of genetic homogeneity among populations in this ecosystem (Diamante et al 2020).…”
Section: Introductionmentioning
confidence: 99%